PENERAPAN PRAKTIK IBADAH SHALAT ANAK TUNARUNGU DI SLB NEGERI BANYUATES - Amaliya Mufarroha; Faizetul Ukhrawiyah; Fauziyah Kurniawati (MA'ALIM: Jurnal Pendidikan Islam, 2025)
Guiding and educating children to perform the prayer ritual is a commandment. In Islam, prayer is a key pillar that holds a central position in the religious life of Muslims. Through religious education, particularly regarding prayer from an early age, children can be encouraged to understand and develop a love for their religion. Deaf children, although experiencing a relatively slow development compared to children in general, still possess potential that can be developed, especially with appropriate guidance methods. From an Islamic perspective, children with special needs remain individuals who deserve attention for the benefit of their lives, even though they do not yet have full obligations to carry out religious laws. Children with special needs experience obstacles in the learning and development process, so they require educational services tailored to their character and learning needs. This research ams to determine how the practice of prayer for deaf children is implemented at the Banyuates State Special School for the Special Needs. This research used qualitative field methods, with data collection techniques including interviews and observations. The research results show that the implementation of prayer practices for deaf children at Banyuates State Special School is carried out through a learning method of habituation and practice (drill). The deaf children at Banyuates State Special School can follow the prayer movements well, and the school also implements congregational Dhuhr prayer. This helps the children become accustomed to and fluent in following the prayer movements even though they don't know the prayer recitations by heart.